Optical Optimization with Microstructure Evolution Inspired from Lepidopteran Scales. Issue 16 (31st May 2022) - Zhao, Xinkun; Wang, Wanlin; Zhang, Wang; Wang, Bo; Li, Jiyou; Zhang, Di
Abstract: Lepidopteran scales exhibit exquisite architectures that produce complex optical performance, such as structural colors for multiple survival strategies. However, how do these optical properties evolve to achieve such an excellent performance remains enigmatic because of the rarity of fossils and complexity of the gene regulatory network. Here, inspired by the primitive lepidopteran fossils, it is deduced that the morphology of these multilayered scales can be expressed by the basic trigonometric function sin( x ) = t . A unified evolving model (UEM) is developed to reconstruct the evolutionary process from original multilayers to the current lepidopteran scale microstructures. The simulated optical response results show that factors such as the light absorption, warning coloration, and visual range intensity are optimized for survival by these insect individuals. The UEM provides a route to rationalizing other natural periodic microstructures. Furthermore, microstructure parameterization can facilitate the design of the nano‐optical materials. Corresponding results can help develop specific applications such as photothermal conversion, radiative cooling, and camouflaging. Abstract : Lepidopteran scales exhibit exquisite architectures that produce complex optical performance. Here a unified evolving model is developed to reconstruct the evolutionary process. Simulated results indicate that their optical properties are optimized for survival strategies. The model can inspire applications of similar evolutionary and formational principles to the preparation of advanced optical materials.